Neurotransmitter amino acid adsorption on metal doped boron nitride nanosheets as biosensor: DFT study on neural disease prediagnosis system - Balkanli, Bugracan; Yuksel, Numan; Fellah, M. Ferdi (Elsevier Science Sa, 2024)
In this study, pristine and iron (Fe), copper (Cu) and platinum (Pt) metal doped boron nitride nanosheet (BNNS) structures possibility of biosensor, adsorbent and neural disease prediagnosis system for gama amino butyric acid (GABA) and Glutamate (Glu) molecules were investigated by Density Functional Theory (DFT). Metal atoms were doped to replace both boron (B) and nitrogen (N) atoms of BNNS. All the adsorption energies on the structure were calculated as negative values for all structures after the GABA and Glu adsorption. The lowest adsorption energy and enthalpy values reached to - 42.1 kcal/mol and - 42.7 kcal/mol, respectively. According to Gibbs free energy (Delta G) values of adsorption, most of the adsorption reactions can occur spontaneously. The charge transfer during adsorption happened from GABA and Glu molecules to BNNS structures. Based on the results, Fedoped BNNS and Cu-doped BNNS could be utilized as electronic and work function type biosensors for GABA molecule and Glu molecule respectively. This study may lead to future biosensor studies, adsorption studies of neurotransmitter amino acids other than GABA and Glu, and BN nanostructure studies modified with different metal doping.
Keywords: DFT; BNNS; Neurotransmitter; Adsorption; Detection; Biosensor